Impact of perceived course of illness on the desire for social distance towards people with symptoms of schizophrenia in Hanoi, Vietnam. (October 2018) - Martensen, Lara Kim; Hahn, Eric; Cao, Tien Duc; Schomerus, Georg; Nguyen, Main Huong; Böge, Kerem; Nguyen, Tat Dinh; Mungee, Aditya; Dettling, Michael; Angermeyer, Matthias C; Ta, Thi Minh Tam
Highlights: First insights about desire for social distance towards psychosis patients in Vietnam. Expected unfavourable social functioning was associated with more social distance. Expected lifelong dependency was associated with more social distance. Strengthening social functioning of patients may reduce public stigma. Abstract: In Vietnam, stigmatisation and discrimination of patients with mental illness are highly prevalent. This study explores whether the perception of course of illness of people with symptoms indicating schizophrenia is associated with the desire for social distance in the Vietnamese public. A population-based survey ( n  = 455) using unlabelled vignettes for schizophrenia was carried out in the Hanoi municipality in 2013. First, a factor analysis was performed to group items indicating perception of prognosis. Second, a linear regression analysis was used to search for correlations between these expectations and desire for social distance. The factor analysis revealed three independent factors of perception of course of illness: (1) loss of social integration and functioning, (2) lifelong dependency on others, and (3) positive expectations towards treatment outcome . Both factors with negative prognostic perceptions (1&2) were associated with more desire for social distance. The results indicate a link between social acceptance and the perceived ability to maintain a social role including a capability of reciprocity within the Vietnamese society. Additionally, these findings highlight the importance of preserving social functioning in any treatment approach for patients with schizophrenia, which includes psychosocial intervention and rehabilitation programs.